- Uji Aktivitas Antibakteri Ekstrak Etanol Daun Tapak Liman (Elephantopus Scaber L ) Terhadap Bakteri Shigella Dysenteriae Dengan Metode Difusi Cakra, : UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN TAPAK LIMAN (Elephantopus Scaber L) TERHADAP BAKTERI SHIGELLA DYSENTERIAE DENGAN METODE DIFUSI CAKRAM - Zendrato, Baby Cikita Lestari; Nasution, Sri Wahyuni; Lubis, Nursoleha; Silaban, Saharan R (Biospecies, 2021)
Dysentery is an inflammation of the intestine caused by shigella bacteria which can lead to physiological disorders and becomes a health problem that needs to be considered. Liman Tread Leaves ( Elephantopus scaber ) contains high flavonoid compounds, phenols and saponins which are reported to have antioxidants, antibacterial, antiviral and anti-inflammation. This study aims to find out the activity of ethanol extract of liman tread leaves ( Elephantopus Scaber L ) as an antibacterial and to find out the minimum microbial death rate value for Shigella spp bacteria. This research uses the True Experimental Post-Test Only Control Group Design where Liman Tread Leaves are extracted by maceration method and placed on MHA media overgrown by bacteria. Based on the statistics test results using regression test, the t-count value is 4,336 > 2,178 showing an influence of Liman Tread Leaf extract with a bland zone of 65.4%.